Legal Protection of Marks in the Perspective of Property Rights Law - Ayi Winarsasi, Putri; Orba Manullang, Sardjana; Asiyah; Adipradana Setiawan, Yogabakti; Al-Khalaf, Awad (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Institut Agama Islam Negeri Sultan Amai Gorontalo, 2023)
The brand is the manufacturer's public persona, a barometer of the company's public standing, and a watershed moment in the company's overall business strategy. There's no getting around the fact that a product's brand serves as its identity; after all, it's what sets one firm apart from another. The protection of registered marks, however, is sometimes the source of intricate legal challenges that obscure the mark's true significance. The purpose of this research is to evaluate and analyze the legal protection of registered trademarks and to determine the reason of the termination of its protection using a normative juridical approach. The research uncovered a number of potential triggers for a brand's registration to be revoked, such as the end of the brand's validity period, a request for revocation by the brand's owner, ministerial initiative based on the recommendation of the brand appeal Commission, or a lawsuit filed by a third party. Once the trademark is registered, it is protected for a certain length of time that may be extended. Legal action, criminal prosecution, and administrative measures like trademark cancellation or registration rejection all serve as deterrents. Defending corporate identities through trademarks is crucial in today's period of intense global competition. This study delves deeply into the value of brands to manufacturers and the legal hurdles that must be overcome to ensure a brand's long-term viability in a competitive market. With this knowledge in hand, company stakeholders may take the necessary initiatives to establish a brand that will endure. Protecting your name and your ideas are essential.